The Effect Of Work Discipline And Work Motivation On Employee Work Productivity At The Mulak Ulu District Office Lahat Regency - Yunita Nurul Hasanah; Hestin Hestin; Rudi Eduar (Journal of Management, Economic, and Accounting, 2026)
The purpose of this study was to determine the effect of work discipline and work motivation on employee work productivity at the Mulak Ulu Sub-district Office, Lahat Regency.The results of the study showed that (1) work discipline has a significant partial effect on work productivity, as evidenced by the calculated t value > t-table (5.205 > 2.005). (2) work motivation has a significant partial effect on work productivity, as evidenced by the calculated t value > t-table (2.177 > 2.005). (3) Work Discipline and Work Motivation have a significant simultaneous influence on Employee Work Productivity at the Mulak Ulu Sub-district Office, Lahat Regency. This can be seen from the calculated f value > f table (59.997 > 2.005) and the significance value is smaller than the significance level (a) of 0.05 (0.000 < 0.05).